PAI Teachers' Interpersonal Communication in Increasing Students' Learning Motivation in PAI Subjects (Case Study at SMA Jati Agung Wage Taman Sidoarjo) - Ady Ubaidillah (LP2M IAI AL-KHAIRAT PAMEKASSAN, 2026)
This study aims to examine the role of interpersonal communication of Islamic Religious Education (PAI) teachers in improving students' learning motivation at SMA Jati Agung Wage Taman Sidoarjo. A descriptive qualitative approach was employed, with data collected through non-participatory observation, semi-structured interviews, and documentation. Informants included the principal, PAI teacher, class XI homeroom teacher, and class XI students. Findings revealed that: (1) the PAI teacher's interpersonal communication was effective and positively influenced students' learning motivation; (2) students' learning motivation was affected by internal factors such as physical and psychological conditions, as well as external factors including family environment, peers, and classroom conditions; (3) the PAI teacher implemented various motivational strategies including innovative teaching methods, empathetic approach, effective verbal and nonverbal communication, and integration of Islamic values. These findings imply that interpersonal communication competence is an essential skill for PAI teachers in creating conducive and meaningful learning environments.